The microstructural characteristics in a superalloy hybrid component fabricated by friction process - Tra, Tran Hung; Sano, Atsushi (Vietnam Journal of Science and Technology, 2017)
The dissimilar superalloys joint between Inconel 718 and Mar-M247 is fabricated by friction welding technique. The microstructure in and around the welding is investigated by the Scanning electron microscope (SEM) and Energy-dispersive X-ray spectroscopy (EDS). The welding is found to be free defects and the welded zone is quite narrow. The diffused zone between the two base metal is tine. The microstructure in the welded zone is recrystallized significantly and reveals a very complicated morphology and characteristics in Inconel 718 side. Inconel 718 and Mar-M247 could be joined successfully by the friction technique.